The coronal sealing ability of an experimental nano hydroxy apatite-containing endodontic sealer: in vitro study - A. Alomari, Shadi M (2008)
The coronal sealing of root canal filling is of crucial importance for the longterm success of root canal treatment, as the coronal leakage of bacteria and other irritants to the root canal system, is one of the main factors that may result in clinical failure of endodontic treatment. A new experimental nano hydroxyapatite containing endodontic sealer was developed by the School of Dental Sciences, USM, Kubang Kerian, Kelantan, Malaysia, for commercialization. The purpose of this study was to compare the coronal sealing ability of the new sealer with that of AH26 silver free sealer before and after preparation for post, and to study the effect of post space preparation, and the effect of EDT A pretreatment on the coronal sealing ability of both sealers. A total of 228 extracted single rooted human teeth were used. Crowns were amputated using a hard tissue cutter, leaving roots of 13 mm length. Each root canal was cleaned and shaped using K-files and step back technique. The prepared roots were randomly divided into 6 experimental groups, with 38 teeth in each group. Roots in all groups were obturated using the lateral condensation technique. Nano HA sealer was used in the first group, while AH26 was used in the second group. In the third group, teeth were obturated using nano HA sealer, and after one week they were prepared for post. The fourth group was treated the same as the third group, but using AH26 sealer. In group five, roots were treated with EDT A solution, before being obturated using nano HA sealer. In group six, roots were treated with EDT A solution, and then obturated using AH26 sealer. All teeth were stored in an incubator at 3 7°C for 7 days to allow adequate setting of sealers. After that all teeth were thermo cycled between 5°C and 55°C, with an immersion time of 30 seconds in each path, for a total of 500 cycles. Root surfaces were completely covered by two layers of nail varnish, except the coronal opening, and then they were placed in methylene blue dye. After 24 hours, all teeth were washed under running water and sectioned vertically. Coronal dye leakage in each tooth was measured in mm using light microscope supported by image analyzer software. Data was entered into SPSS software and analyzed using independent t test. No significant difference in the coronal leakage of dye was found between the two sealers, both before and after preparation for post, where p value was 0.410 and 0.078 respectively. Groups prepared for post leaked significantly more than groups not prepared for post, with p value 0.012 and 0.014 for nano HA and AH26 sealers respectively. Groups treated with EDT A leaked significantly less than groups with no such pretreatment, where p value was 0.006 and 0.031 for nano HA and AH26 sealers respectively. It was concluded that no significant difference was found in the coronal sealing ability between the two sealers, both before and after post space preparation. The preparation for post decreased the coronal sealing ability of both sealers; while pretreatment of prepared canals with EDT A improved the coronal sealing ability of both sealers.